CENTA as a Chromogenic Substrate for Studying β-Lactamases - Bebrone, Carine (American Society for Microbiology, 2001)
CENTA, a chromogenic cephalosporin, is readily hydrolyzed by β-lactamases of all classes except for the Aeromonas hydrophila metalloenzyme. Although it cannot practically be used for the detection of β-lactamase-producing strains on agar plates, it should be quite useful for kinetic studies and the detection of the enzymes in crude extracts and chromatographic fractions.